Los Sonetos de Calderón en sus obras dramáticos : Estudio y edición - Osuna, Rafael (University of North Carolina publications of the Department of Romance Languages., 2019)
A study of the somewhat parsimonious but intentional use of multiple sonnets in Calderon's drama.